The Influence of Fujianti Utami's Credibility And Authenticity On Consumer Purchase Intention - Majid, Musfirah; Rosanti, Cholisa (JURNAL ILMU MANAJEMEN, 2025)
This study was conducted to gain a deeper understanding of the influence of Fujianti Utami’s credibility and authenticity as a social media influencer on consumer purchase intention. The research method involved distributing structured questionnaires to a purposive sample of the Indonesian public through online platforms. The sampling method used was purposive sampling, with a total of 60 respondents who met the following criteria: (1) at least 17 years old, (2) actively use social media platforms such as Instagram, TikTok, or Twitter/X, and (3) have either used or never used influencer marketing services. The collected data were analyzed using Statistics and Data (STATA) software to examine the causal relationship between variables. The results showed that out of the 60 responses, 18.48% of respondents selected credibility, including factors such as expertise, trustworthiness, and reliability as a factor influencing their purchase decision, while an average of 19.48% chose influencer authenticity, which includes honesty, transparency, and personal storytelling. Based on these findings, it can be concluded that influencer authenticity is perceived as a more influential factor in shaping consumer attitudes, emotional engagement, and brand trust, ultimately affecting consumer behavior and increasing purchase intention in the context of digital marketing and influencer-driven campaigns.